ANALYSIS OF STUDENTS' IMPOSTOR PHENOMENON: SELF-ESTEEM AND ATYCHIPHOBIA IN MATHEMATICS LEARNING - Hayati, Nurul; Winarso, Widodo; Sofhya, Herlinda Nur'afwa (JURNAL EDUSCIENCE, 2024)
This study aims to analyze the impostor phenomenon of students and its relationship with self-esteem and atychiphobia in mathematics learning at SMA Negeri 1 Gegesik. This study uses a qualitative method with a case study design and criterion sampling technique. The subjects of the study were 143 grade XI students, where 8 students were identified as experiencing the impostor phenomenon with the criteria "Very High". These findings indicate a moderate negative correlation between the impostor phenomenon and self-esteem, and a positive correlation between the impostor phenomenon and atychiphobia. The implications of this study are the importance of focused psychological interventions to overcome the impostor phenomenon and atychiphobia, as well as self-esteem development programs that can help students increase their self-confidence in academic contexts, especially in mathematics.